STRATEGI PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN FOKUS ANAK DI TK PELITA BUNDA KABUPATEN SELUMA - Elisna Hikma Nelsi; Nurhafizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low focus of early childhood learning at Pelita Bunda Kindergarten, Seluma Regency which is characterized by lack of attention, easily distracted, and low involvement in learning activities. This research aims to increase children's learning focus through the application of contextual learning strategies. The method used is the Kemmis and McTaggart model Class Action Research (PTK) which includes the stages of planning, action, observation, and reflection. The research was carried out in two cycles with 8 research subjects in group B. Data collection techniques used observation and documentation, while data analysis was carried out in a quantitative descriptive manner. The results showed that the percentage of children who achieved the categories of Performing Well as Expected (BSH) and Performing Very Good (BSB) increased from 25% in pre-cycle to 37.5% in Cycle I and reached 87.5% in Cycle II. These findings show that contextual learning strategies are effective in increasing children's learning focus through activities that connect real experiences with the learning process. Thus, contextual learning strategies can be an effective learning alternative to improve early childhood